Biotization of Endophytes Trichoderma asperellum and Bacillus subtilis in Mentha spicata Microplants to Promote Growth, Pathogen Tolerance and Specialized Plant Metabolites (2022)
ABSTRACT: In the present study, the effect of biotization of Mentha spicata microplants with Trichoderma asperellum and Bacillus subtilis on growth, Rhizoctonia sp., incidence, and specialized metabolites content was evaluated. Analyses of root tissues of the microplants showed 100% endophytism with both microorganisms. During the acclimatization phase, plants with the endophytes T. asperellum and B. subtilis had a survival rate of 95% and 93%, respectively, compared to 75% for control plants. Then, under greenhouse conditions, a trial was carried out with biotized plants with or without Rhizoctonia sp. inoculation, plants inoculated with Rhizoctonia sp., and endophyte- and pathogen-free control. Biotized plants with the endophytes showed higher dry biomass and the incidence of Rhizoctonia was lower (8% for T. asperellum and 10% for B. subtilis) compared to plants inoculated with the pathogen (82%). In addition, plants with T. asperellum had the highest contents of total polyphenols (280 GAE/100 mg sample) and rosmarinic acid (28 mg RA/100 g sample). Thus, this study shows the potential of the technique of using the endophytes T. asperellum and B. subtilis on M. spicata microplants to improve plant survival and growth, decrease the incidence of Rhizoctonia sp., and improve the contents of specialized metabolites, which can contribute to the sustainable management of this crop.